Pengaruh Konsentrasi Garam Yang Berbeda Terhadap Karakteristik Mutu Ikan Kembung (Restrelliger Kanagurata) Asin Dengan Metode Penggaraman Kering (Dry Salting) - Moh Azrul; Mile, Lukman; Djailani, Fernandy (Transbahasa, 2024)
This research aims to determine the influence of different salt concentration on the quality characteristics of salted mackerel fhis (restreliger kanagurata) using the dry salting method. This research consists of three treatmen factors with three replications, namely salt concentrations of 5%, 15%, and 25%. The data analysis employs a Completely Randomized Designe (CRP) and is futher tested using Duncan’s method. The best treatmen was determined using De Garmo analysis. The results indicate that the best treatmen for processing dry salted mackerel fhis was whit a salt concentration of 15%, which obtained organoleptic values with the following quality specifications: intact appearance, moderately clean, satisfactory taste, specific type, without additional flavor, solid texture, compact, flexible, moderately dry, nearly natural odor, and slightly added odor. The moisture content was 11.83%, the ash content was 1.49%, and the total plate count was 8.06 x 103.